Electronic Detection and Diagnosis of Complex Regional Pain Syndrome - Hahn, Ashly; Park, Noella (Technium BioChemMed, 2024)
Complex Regional Pain Syndrome (CRPS) is a chronic disease that is random and abrupt. As a result, an accurate diagnosis and treatment have yet to be identified due to numerous symptoms and causes. Currently, the method of diagnosis of CRPS is the Budapest Criteria. However, this criterion relies on the patient and doctor’s subjective judgments. Therefore, we propose to develop a diagnostic method for CRPS, integrating reliable and objective analysis of common patterns that occur in patients’ genetic and neuronal structures. Utilizing a zinc oxide biosensor, it was shown the patients’ blood samples with high concentrations of MMP-9, and neuroinflammation occurs as the immune system is impaired. By analyzing blood samples, we quantified the number of CD4+ T cells that penetrate nerves, with direct human CD4+ T cell counting. We compared the structure of neuron cells and identified damage in CRPS patients that were located primarily on dendrites. The significance of using DNA detection and neuron biochips will dramatically improve the diagnosis and treatment of CRPS.